ANALYSIS OF THE NATURE OF WORKS TO NEAR MISS EVENT AT CARING UNIT OF CIMACAN GENERAL HOSPITAL - Mugi Restiana Utami (Universitas Muhammadiyah Semarang, 2017)
Patient safety is an injury prevention system for patients by reducing the risk of adverse events associated with exposure to the diagnostic environment or medical treatment conditions. One of the factors that contribute to the patient's safety incident is the nature of work.The aim of this study is to analyze of the nature of works on near miss event (NME) at Cimacan General Hospital. This researchwas a descriptive quantitative research using secondary data from incident report and related document.There were 7 reports of NME in caring unit at Cimacan general hospital. Data analysis used descriptive analysis. Result of descriptive analysis, 5 respondents (71,83%) was non complex treatment, 2 respondents (28,73%) was complex treatment. Six respondents (85.7%) did not comply on procedures, 1 respondent (14.3%) adhered to procedures. Seven respondents (100%) were present at the time of near miss. Analysis of the nature of work on NME is an uncomplicated treatment, non-compliance with procedure, and present at the time of NME. Keywords: nature of work, near miss event, patient safety